2019
DOI: 10.1021/acs.biochem.9b00100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Filamin A Mechanobinding Partner I: Smoothelin Specifically Interacts with the Filamin A Mechanosensitive Domain 21

Abstract: Filamin A (FLNA) is a ubiquitously expressed actin cross-linking protein and a scaffold of numerous binding partners to regulate cell proliferation, migration, and survival. FLNA is a homodimer, and each subunit has an N-terminal actin-binding domain followed by 24 immunoglobulin-like repeats (R). FLNA mediates mechanotransduction by force-induced conformational changes of its cryptic integrin-binding site on R21. Here, we identified two novel FLNA-binding partners, smoothelins (SMTN A and B) and leucine zippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…These novel finding is supported by the work of the group of Nakamura, who found out by SILAC‐based quantitative proteomics that synaptopodin is a potential interaction partner of filamin A. In addition, they identified a filamin A binding motif in the synaptopodin protein sequence by in silico screening 59 …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These novel finding is supported by the work of the group of Nakamura, who found out by SILAC‐based quantitative proteomics that synaptopodin is a potential interaction partner of filamin A. In addition, they identified a filamin A binding motif in the synaptopodin protein sequence by in silico screening 59 …”
Section: Discussionmentioning
confidence: 69%
“…In addition, they identified a filamin A binding motif in the synaptopodin protein sequence by in silico screening. 59 Furthermore, we found that the expression of other actinassociated and podocyte-specific proteins such as ezrin, palladin, fascin-1 and Inf2 were also significantly downregulated in Flna KO podocytes suggesting an important role of filamin A for the regulation of proteins that are involved in actin dynamics as well as for cell adhesion. 45,[60][61][62][63] Pinto and coworkers have shown that mechanoprotection by filamin A occurs via an activation and expression of focal adhesion proteins.…”
Section: F I G U R Ementioning
confidence: 74%
“…Nevertheless, many known AAPs possess uncharacterized ABD (smoothelin, fimbacin, etc.) [76,77] (Figure 3 and Table S1). The structural geometry of AAPs influences their binding strength to actin filaments.…”
Section: How Abps Interact With Actinmentioning
confidence: 99%
“…Although we only listed actin-AAP complexes that currently exist in the protein dat bank, computational analysis has also been used to build a model for some ABPs [75 Nevertheless, many known AAPs possess uncharacterized ABD (smoothelin, fimbacin etc.) [76,77] (Figure 3 and Table S1). The structural geometry of AAPs influences thei binding strength to actin filaments.…”
Section: How Abps Interact With Actinmentioning
confidence: 99%
“…In 2011, we listed over 90 filamin binding partners including channels, receptors, intracellular signaling molecules, and even transcription factor [2]. In the past ten years, the list of filamin binding partners has been expanded and is still expanding [35,36]. Considering the sequence similarity of filamin isoforms, FLNC likely interacts with most of these numerous binding partners if they are co-expressed, although one binding partners has been shown to only interact with filamin A [37].…”
Section: Flnc Binding Partnersmentioning
confidence: 99%